Small hydropower—Small ecological footprint? A multi-annual environmental impact analysis using aquatic macroinvertebrates as bioindicators. Part 2: Effects on functional diversity - Scotti, Alberto; Jacobsen, Dean; Bottarin, Roberta (Frontiers in Environmental Science, 2022)
Currently, across the entire European river network, there are an estimated 0.74 barriers per kilometer of river length, with hydropower production being the main cause of riverine habitat fragmentation. On the one hand, policy actions have been proposed by different institutions to limit this impact. On the other hand, the compelling need to produce energy from renewable/sustainable resources is further boosting the impoundment of rivers, since, globally, small hydropower plants are expected to contribute greatly to future energy needs. While a few studies have already analyzed the environmental impact of small hydropower plants by researching the structural communities of benthic macroinvertebrates, none have thus far assessed the potential impacts related to the functional diversity of these communities. Here, following a “Before-After-Control-Impact (BACI)” scheme, we implemented different methodologies to study the functional diversity of benthic communities sampled across 4 sites in a fish-free, glacier-fed stream of the Italian Central-Eastern Alps for 5 consecutive years. More specifically, the sampling sites were chosen in an area near the weir of a small “run-of-river” hydropower plant, which constituted the structure from which water was diverted to the turbine. Specific goals were to assess the potential variation in the functional traits of benthic macroinvertebrates in relation to the weir’s presence, investigate whether a variation in trait distribution was caused by alterations in the abundances of common and rare taxa, and quantify functional diversity in space and time through the application of specific indices. Our initial hypothesis of finding significant differences among the sampling sites after the start-up of the hydropower plant was not confirmed by our results, since the benthic communities at all sites continued to exhibit a largely similar set of traits and, consequently, functional diversity. Our results highlighted the need for a better understanding of the relationships between effect traits and ecological processes to establish thresholds from which a shift in these processes may occur. Hence, a better understanding of the assets and liabilities of already established small hydropower plants may be a guide for more conscious decisions concerning the establishment of new ones and/or changes in the management of already existing ones.